Challenges of Developing a Logistics Hub Case Study: Batu Ampar Port - Mulia Pamadi; Yusra Aulia Sari (Diponegoro University, 2022)
As a region with leading sectors of marine, tourism, industry, fisheries, and Batu Ampar as the Main Port, Batam has the potential to be developed. One of the main centers of activity is large ports and international airports that can become national and international-scale economic gateways for logistics hubs. This research aimed to determine The Challenges of developing a logistics hub in Batu Ampar Port. This research uses a descriptive qualitative approach and secondary data from the Batam port office and the Human Settlements and Spatial Planning Office. This research shows some challenges such as geography, infrastructure, connectivity, transportation costs and time, Trade movement requirements, Shipping dependability, Transport, and trade regulations. Poor logistics performance is a significant obstacle to trade growth in most Indonesian cities. In this case, there is an international shipping port that does not yet have adequate facilities and infrastructure to become a logistics hub.